The role of CXCR3/LRP1 cross-talk in the invasion of primary brain tumors - Kevin Boyé (Nature Portfolio, 2017)
The chemokine receptor CXCR3-A is expressed in high grade glioma. Here the authors show that CXCR3-A interacts with LPR1, a protein highly expressed in glioma, and this interaction regulates the trafficking of the receptor ultimately impacting on tumour cell migration.